Pertanggungan Asuransi Jiwa Saat Pandemi Covid-19 Dikaitkan Dengan Tingkat Kesehatan Perusahaan Asuransi Berdasarkan Hukum Asuransi - Haikal Yushendri, Muhammad; Karsona, H. Agus Mulya; Rahmawati, Ema (Universitas Medan Area, 2023)
This issue is focused on the liability of life insurance in the conditions of the COVID-19 virus in terms of statutory regulations. In insurance, it is necessary to know the risks broadly which is an essential basis for understanding and knowing the concepts and techniques of risk management. The concept of risk is needed to analyze various ways to protect the insured object. The company is always faced with risks so that risk is part of the company's activities. The data were collected through literature and interviews and analyzed descriptively and qualitatively. This study concludes that life insurance coverage, specifically for the COVID-19 virus, is implemented by applying the principle of freedom of contract as a form of implementing the principle of good faith of insurance companies as insurers to provide good service to policyholders, even though pandemic coverage is not a category of protection established by every insurance company. There is no specific regulation providing legal certainty to insurance companies in providing their services.